DSMUS 1.0 - Redondo, Sergio; Sainz, Héctor; Chacón, Arucas (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
This paper shows how we have developed a video game for Nintendo DS in order to play “Mus”, one of the most popular Spanish card games, thereby we considered designing a video game would be an interesting way of applying our acquired knowledge about artificial intelligence.
Keywords: artificial inteligent; case-based reasoning; mus; IJIMAI; IJIMAI